The Remediation of Integer Operations Misconceptions for Seventh-Grade Students Through Role-Playing Approach - Zubatasari, Ayu Puspita; Sugiatno, Sugiatno; Siregar, Nurfadilah (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Kerinci, 2025)
Misconceptions in integer operations remain a common challenge among junior high school students, affecting their understanding of mathematical concepts and procedures. This study aimed to remediate these misconceptions through a role-playing approach that integrates physical and contextual learning experiences. The participants were five seventh-grade students from a junior high school in West Kalimantan, Indonesia, selected based on diagnostic test results and teacher recommendations. A descriptive qualitative design was employed, with data collected through tests, observations, interviews, and documentation. The remediation process was carried out in four systematic stages involving role simulation with physical number lines, group discussions, contextual problem-solving, and reflection. The findings revealed that students successfully overcame conceptual, procedural, and operational misconceptions, while representational misconceptions decreased considerably though still persisted in some students. Role-playing proved effective in fostering engagement and conceptual reconstruction, indicating its potential as an alternative strategy for misconception remediation. Further enhancement of visualization tools, such as number line media or digital supports, is recommended to optimize learning outcomes.